2017
DOI: 10.1038/s41598-017-05760-9
|View full text |Cite
|
Sign up to set email alerts
|

The LRRK2 G2385R variant is a partial loss-of-function mutation that affects synaptic vesicle trafficking through altered protein interactions

Abstract: Mutations in the Leucine-rich repeat kinase 2 gene (LRRK2) are associated with familial Parkinson’s disease (PD). LRRK2 protein contains several functional domains, including protein-protein interaction domains at its N- and C-termini. In this study, we analyzed the functional features attributed to LRRK2 by its N- and C-terminal domains. We combined TIRF microscopy and synaptopHluorin assay to visualize synaptic vesicle trafficking. We found that N- and C-terminal domains have opposite impact on synaptic vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 48 publications
(74 reference statements)
4
52
0
Order By: Relevance
“…We observed that the E193K variant increases SV fusion. Interestingly, we and other have reported a similar phenotype upon LRRK2 silencing 4,5,31 . Furthermore, we were able to rescue the SV phenotype correlated with E193K upon co-expression of the isolated N-terminal domain.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We observed that the E193K variant increases SV fusion. Interestingly, we and other have reported a similar phenotype upon LRRK2 silencing 4,5,31 . Furthermore, we were able to rescue the SV phenotype correlated with E193K upon co-expression of the isolated N-terminal domain.…”
Section: Discussionsupporting
confidence: 81%
“…Our data are consistent with such model and suggest that the N-terminal and C-terminal domains act together to shape the interacting site for SV and SV-associated proteins. www.nature.com/scientificreports www.nature.com/scientificreports/ However, we reported that the isolated LRRK2-WD40 domain prevents SV fusion by itself 4,6 . In contrast, the isolated N-terminal fragment did not elicit an overt effect on SV dynamics.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These data support our model that the WD40:WD40 protomer interface is important for the formation of LRRK2 filaments. Given the correlation between breaking the dimerization interface, loss of filament formation, and change in kinase activity seen in the G2385 LRRK2 mutant (9,11,(30)(31)(32), supporting that oligomerization plays a role in regulating LRRK2 kinase activity. Here, we have shown that recent advances in cryo-ET can be used to determine novel structures of proteins in situ, making it possible to generate structural hypotheses in a cellular context.…”
mentioning
confidence: 96%